Evaluation of existing and desired measures to monitor, prevent and control healthcare-associated infections in Swiss hospitals (Swiss Medical Weekly, 2021)
OBJECTIVESOptimal surveillance and prevention of healthcare-associated infections (HAI) are crucial for a well-functioning health care system. With a view to establishing a national state-of-the-art programme for surveillance and prevention of HAIs, the Swiss National Center for Infection Control, Swissnoso, developed a survey to explore the options for expanding the existing Swiss HAI surveillance system.METHODSAn online survey was sent to all Swiss acute care hospitals. Local infection prevention and control (IPC) professionals were asked to answer on behalf of their institutions. The questions covered the structure and organisation of IPC programmes, current preventive measures, availability and capacity of electronic medical record (EMR) systems, and ability and willingness to establish and participate in the proposed new surveillance modules. An invitation was sent to the 156 acute care hospitals and hospital networks in June 2020. Responses were collected up to the end of August 2020.RESULTSNinety-four hospitals and hospital networks out of 156 (60%) completed the survey. Among 84 hospitals reporting the number of acute care beds, 61 (73%) were small (650 beds). Twenty-nine different EMR systems were used in the participating hospitals. Twenty-two hospitals were using a different EMR system in their intensive care unit. There were 17 hospitals (18%) without an EMR system but which planned to introduce one soon, and eight small hospitals (9%) neither had an EMR system nor were preparing to introduce one. Surveillance for central-line associated bloodstream infection, catheter-associated urinary tract infection and ventilator-associated pneumonia were already established in 26 (28%), 15 (16%) and 15 (16%) hospitals, respectively. Thirty hospitals (36%) would be willing to participate in the pilot phase of a new surveillance system. Of these, 15 stated that they wanted to be part of the pilot hospital network, 6 could provide hospital-wide surveillance denominators (such as catheter-days and patient-days) to compute incidence rates, and 8 indicated interest in doing both. Large hospitals interested in participating in the pilot phase reported more full-time equivalent staff available for surveillance activities than those who did not declare an interest.CONCLUSIONSBaseline information on hospital IPC structure and process indicators are essential for the roll-out of national surveillance programmes and for improving surveillance activities. Having an EMR system in place and adequate personnel resources dedicated for surveillance activities are crucial prerequisites for developing and implementing an effective HAI surveillance system. The lack of an EMR system and the diversity and capacities of EMR solutions will be the main challenges for successful implementation of national HAI surveillance modules.